Coding-aware secure routing for multi-hop wireless networks - Xian GUO; Tao FENG; Zhan-ting YUAN (Tongxin xuebao)
To address security issues of DCAR in“coding+routing”discovery,a new security destination was proposed and a distributed coding-aware secure routing(DCASR)was designed.DCASR guarantees discovery of correct coding opportunity and establishment of trusted routes by using cryptography.To analyze the properties of DCASR,LS2(logic of security systems)was extended,and a new logic LS2-RP(LS2 for routing protocol)was proposed.In LS2-RP,the concepts of location and neighboring location of thread were introduced.The dynamic topology of multi-hop wireless networks was described by the set of neighbors for thread.The broadcast rule of neighboring location threads modeled the feature of wireless broadcast communication.Finally,DCASR was described by programming language of LS2-RP and security properties were defined by predicates and modal formulas of LS2-RP.Security of DCASR was analyzed by using the proof system of LS2-RP.DCASR can satisfy our secure destination.